Biological Taxonomy as an Extended Analogy in Translation Research: Structuring and Investigating the Relations between Texts - Tringham, Damon (Suomen kääntäjien ja tulkkien liitto – Finlands översättar- och tolkförbund ry, 2025)
This paper focuses on how a biological concept can be utilised as a translational tool. This takes the form of an extended analogy that constitutes a viable and useful aid in research. My basis is the terms and categories of biological taxonomy and speciation as commonly understood, and how these may be applied to the study of the translation of novels, in my case the Discworld series by Terry Pratchett. The paper introduces the use of metaphors and analogies used both about and in translation studies, discussing these to demonstrate how they differ from mine. I justify the use of analogy as a tool before presenting a biological analogy used to aid creativity in my research. I show how the analogy was constructed and highlight an initial weakness as an example of potential pitfalls. On the relationship between source text and translation, I reflect upon their sameness or otherwise, looking at how changes made in the language and other features may be considered speciation. I also briefly introduce some parallels created by the analogy that can be explored. My study is thus an exercise in meta-methodology, attempting to introduce a novel way of self-reflection on theoretical thinking.